PENGARUH IKLIM KERJA, GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP SEMANGAT KERJA PEGAWAI SEKRETARIAT DAERAH KOTA SOLOK - Hane Johan; Haderah Haderah (STKIP Pesisir Selatan, 2020)
This study aims to determine: 1) The influence of work climate on job satisfaction of Solok City Regional Secretariat employees, 2) The influence of leadership style on job satisfaction of Solok City Regional Secretariat employees 3) The influence of work climate on employee morale of Solok City Secretariat employees, 4) Effect leadership style on the work spirit of Solok City Regional Secretariat employees, and 5) The effect of job satisfaction on the work spirit of Solok City Regional Secretariat employees.The results of the study revealed that there is a direct influence of Work Climate on job satisfaction of employees of the Solok City Regional Secretariat which consists of the direct influence of Work Climate on satisfaction, the indirect effect of Work Climate on employee job satisfaction through work morale, indirect effect of Work Climate on employee job satisfaction through the Leadership Style. Leadership Style on job satisfaction of Solok City Regional Secretariat employees, which consists of the direct influence of Leadership Style on job satisfaction, and indirect influence of Leadership Style on job satisfaction of Solok City Secretariat employees.the direct influence of the Leadership Style on job satisfaction. The results are greater when compared to the direct effect of Work Climate on employee job satisfaction. the direct influence of work morale variables on job satisfaction of Solok City Secretariat employees.